Sintagmas y paradigmas en "La consagración de la primavera", de Alejo Carpentier - Pérez Miguel, Rafael (Universidad de Costa Rica, 2015)
Time is one of Alejo Carpentier's concerns, and La consagración de la primavera reflects the interest of the Cuban writer in the problem of history. This article intends to show that the syntagmatic structuring of this work follows that of the dialectic materialism of history, and that the paradigmatic structuring in contextualized by several crosscrossing intertexts.